Prevention of stress conditions of students by means of physical culture and sports - Mavropulo O.S. ,; Demyanova L.M. ,; Tashchiyan A.A. ,; Zhikharev D.A. , (Theory and Practice of Physical Culture, 2025)
Abstract Objective of the study was to discover methods for preventing students from experiencing stress through physical activity and sports. Methods and structure of the study. The research was carried out at the Don State Technical University in Rostov-on-Don, involving two groups of second-year students. The experiment took place from January to February 2024. To assess the stress levels of the students, a survey was administered. Results and conclusions. For students experiencing high levels of stress, a tailored set of classes is recommended, which includes physical exercises designed to improve health, enhance the body's resilience, and promote a healthy lifestyle. These activities also help develop perseverance, endurance, and coordination. The study demonstrated the effectiveness of this comprehensive approach.